The Current Development Status of New Financial Products in Vietnam's Banking Market - Do Thu Thuy (South Eastern European Journal of Public Health, 2025)
This study examines the effectiveness of new financial products in Vietnam's banking market, aiming to evaluate their impact on banking performance and the broader financial market's growth. With a focus on digital banking and green financial services, the research identifies key factors affecting the successful adoption and performance of these innovations, such as customer demand, regulatory frameworks, technological advancements, and market competition. By analyzing these dynamics, the study highlights the dual role of new financial products in driving revenue growth and enhancing customer satisfaction. A mixed-method approach was adopted, integrating qualitative insights from interviews with banking professionals and quantitative data from customer surveys and financial reports. The findings reveal that digital banking has significantly streamlined banking operations, reduced transaction costs, and improved accessibility, while green financial services have bolstered sustainable investment opportunities and attracted environmentally conscious customers. However, challenges remain, including gaps in regulatory oversight, uneven technological infrastructure, and varying levels of customer digital literacy. The research offers actionable recommendations for banks, including strategies to enhance product innovation, improve customer education, and strengthen collaborations with Fintech companies. Furthermore, it underscores the need for policymakers to establish a robust legal framework and support technological upgrades to foster an enabling environment for financial innovation. These insights provide valuable guidance for banks seeking to optimize their offerings and for regulators aiming to ensure the sustainable development of Vietnam's financial sector.